2009
DOI: 10.1007/s10800-009-9794-5
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic reaction kinetics and its implication on flow-assisted corrosion of aluminum alloy in aqueous ethylene glycol solution

Abstract: The cathodic reaction kinetics and anodic behavior of Al alloy 3003 in aerated ethylene glycol-water solution, under well-controlled hydrodynamic conditions, were investigated by various measurements using a rotating disk electrode (RDE). The transport and electrochemical parameters for cathodic oxygen reduction were fitted and determined. The results demonstrate that the cathodic reaction is a purely diffusion-controlled process within a certain potential region. The experimentally fitted value of diffusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…All of the tests were mostly restricted to ethylene glycol with different concentrations and inhibitors. used rotating disc electrode (RDE) [4][5][6][7]. This work involved rotating the solution instead of the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…All of the tests were mostly restricted to ethylene glycol with different concentrations and inhibitors. used rotating disc electrode (RDE) [4][5][6][7]. This work involved rotating the solution instead of the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study conducted in Cheng's group [1][2][3][4][5][6][7][8][9] has demonstrated that Al alloy would experience pitting corrosion, flow-assisted corrosion and erosion-corrosion in the automotive cooling system, even in the inhibited coolant. It was reported [10,11] that, although inhibitors have been added in the commercial coolants, i.e., ethylene glycolwater solutions, most of them are not designed for corrosion inhibition of Al alloys, but for stainless steels and copper alloys that have been the conventional materials for fabrication of the automotive heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Ref [1][2][3][4] have demonstrated that aluminum (Al) alloy experiences serious flow-assisted corrosion (FAC) in the automotive cooling system, even in the coolant with a commercial inhibitor addition. It is realized that most of the currently available commercial coolants contain inhibitor that is not designed for Al alloy, but for stainless steels and copper alloys (Ref 5-7).…”
Section: Introductionmentioning
confidence: 99%